H03 Cerebral and extracerebral cholesterol biosynthesis is impaired in Huntington's disease patients. (16th November 2010) - Leoni, V; Mariotti, C; Nanetti, L; Tomasello, C; Salvatore, E; De Michele, G; Soletti, F; Bentivoglio, A; Bandettini di Poggio, M; Abbruzzese, G; Piacentini, S; Squitieri, F; et al.
Abstract : Background: Cholesterol in the CNS is fundamental for membrane trafficking, signal transduction and synaptogenesis and almost all the brain cholesterol is synthetised locally. Homeostasis is maintained through a neuronal specific cholesterol 24-hydroxylase which converts cholesterol into 24-hydroxycholesterol (24OHC). The levels of 24OHC in blood thus reflect the number of active neurons and the volume of the grey matter. We previously found that plasma levels of 24OHC were progressively reduced in early Huntington's disease (HD)1 and that cholesterol biosynthesis was significantly impaired in the brain of multiple mouse HD models, and in fibroblasts of HD patients.2 Methods: We analysed by mass spectrometry plasma levels of the cholesterol precursor lathosterol and lanosterol (marker of cholesterol biosynthesis), 24OHC and bile acid precursor 27-hydroxycholesterol, in 130 HD gene positive subjects (from presymptomatic to advanced stage of disease). Results: We found that plasma levels of lathosterol and lanosterol, together with 24OHC and 27OHC, were reduced in all HD patients compared with healthy controls (p<0.001). Conclusion: Whole body cholesterol synthesis and brain derived 24OHC were significantly decreased following the disease burden. We suggest that the significant decrease in plasma 24OHC levels we reported in early HD1 are associated with two concurrent mechanisms, that is, the progressive loss in grey matter linked to the neurodegenerative process and the impairment in brain cholesterol biosynthesis, in agreement with our previous findings across multiple rodent models of HD2 .